THE USE DISCOVERY LEARNING METHOD IN TEACHING WRITING RECOUNT TEXT TO THE TENTH GRADE OF SMAN NGAMPRAH - Purnamasari, Amel; Argawati, Ningtyas Orilina (IKIP Siliwangi, 2020)
The purpose of this study was to determine the activities that occur during the teaching process of writing Recount Texts using the Discovery Learning method and to identify the benefits obtained by students from writing the Recount Text using the Discovery Learning method in the 2013 curriculum there is one learning model called Discovery Learning. Discovery Learning can help students to learn better because students can think critically and creative. This research is a qualitative descriptive study. The research respondents were English teachers and the tenth grade students of Ngamprah High School. Data obtained from observations and interviews. The results of the study revealed that the results of this study were positive. Students who are taught by using the method of Discovery Learning play an active role in the teaching and learning process. The composition of their writing also shows good results in terms of content, organization, Grammar,vocabulary, and mechanics. Therefore, it is recommended to apply this learning model to teach writing Recount Texts.Keywords: Discovery Learning, Writing Skills, Recount Text